The affect of surgical modifications on early results of pulmonary autograft operation - Romaniuk, A. (Ukrainian Journal of Cardiovascular Surgery, 2016)
The study examines the role of surgical modifications of the pulmonary autograft operation to improve immediate results. Retrospective analysis of 151 operated patients was reviewed, in 82 (54 3%) of these technical innovations have been used: sinus reinforcement of autograft’s root, double suture for aortic anastomosis and creation of the pulmonary artery during ischemic time. The results showed a significant decrease in the number of intraoperative complications, mortality, early complications and improvement in the postoperative period in patients who used the new surgical techniques pulmonary autograft surgery.